MOTIVASI KEBUTUHAN AKAN PENCAPAIAN MERRY PADA NOVEL MERRY RIANA MIMPI SEJUTA DOLLAR KARYA ALBERTHINE ENDAH - Yunita Anas Sriwulandari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2017)
A healthy human consciousness, will be controlling his behavior. Normal behavior is motivated through the conscious process, psychologically most of a person’s behavior is motivated by conscious thought. Motivation is the driving force that makes a person willing and able to exploit the ability in everythings, power and also times for achievement. Motivation is a state within the individual that drives behavior toward achievement. Everyone’s motivation is always different. Motivation is usually studied on the novel character, the term character leads to the perpetrators of the story. Motivation will be more profound if it is realized that every human being has a need that is the need for an achievement. Novel Merry Riana The One Million Dollar Dream by Alberthine Endah deserves to be the object of research, as it presents the motivations and life journey of Merry’s never give up, hardworking, persistent, disciplined, religious and confident to reach her dreams of success. The life principle of Merry Riana in this novel deserves to be an example or a role models for a confused reader living a life full of challenges.